0664 Temporal Patterns of Suicidal Ideation in the Emergency Department. (25th May 2022) - Tubbs, Andrew; Ghani, Sadia; Karp, Jordan; Fernandez, Fabian-Xosé; Klerman, Elizabeth; Perlis, Michael; Grandner, Michael
Abstract: Introduction: Nocturnal wakefulness may be dangerous for vulnerable populations: the incident risk for suicide is highest at night after adjusting for population wakefulness, and nocturnal wakefulness is associated with suicidal ideation. These observations support the hypothesis that sleep- and circadian-dependent changes in mood, reward processing, and executive function increase the risk for disinhibited behavior at night (during periods of nocturnal wakefulness). The present study evaluated this hypothesis by using the timing of emergency department encounters for suicidal ideation. Methods: An archival analysis of data from two emergency departments (EDs) in Tucson, Arizona from 2018 and 2019 yielded 51, 370 encounters for any reason across 29, 359 individuals with usable data, and the time of initial contact was extracted for each case. Of these, 571 individuals (1.94%) sought care for 763 (1.49%) instances of suicidal ideation (determined by ICD-10 code R45.861). Encounters were characterized by date/time, age, sex, race/ethnicity, blood alcohol level (if tested), homelessness, and prior diagnosis of a psychotic disorder, bipolar disorder, or depressive disorder. Suicidal ideation encounters were analyzed as raw counts and as a proportion of all encounters by clock hour and time-of-day categories (night: 12AM-5:59AM; morning: 6AM-11:59AM; afternoon:12PM-5:59PM; evening: 6PM-11:59PM) using robust Poisson models. Results: Although most ED encounters occurred between 6PM and midnight (mean: 9:42PM), the greatest number of suicidal ideation encounters occurred between 12AM and 3AM (mean: 12:18AM). After adjusting for the per-hour proportion of ED visits, the incident risk for a suicidal ideation encounter increased between 8AM and 11AM, peaked at 10AM (IRR: 1.95 [1.10-3.44]) and was lowest at 4PM (IRR: 0.54 [0.32-0.91]). Compared to the evening, the incident risk of suicidal ideation was 64% greater in the morning (IRR: 1.64 [1.31-2.06]), 25% greater at night (IRR: 1.25 [1.00-1.56]), but not different for afternoon encounters. Conclusion: After adjusting for overall encounter rates, ED encounters for suicidal ideation are more likely to occur in the morning. Although the morning peak in incident risk is later than the reported nocturnal risk for incident suicide, this may reflect a delay between when an individual develops suicidal ideation and when they seek or receive treatment. Support (If Any):